Functional and distinct roles of Piezo2-mediated mechanotransduction in dental primary afferent neurons - Lee, Pa Reum; Lee, Kihwan; Park, Ji Min; Kim, Shinae; Oh, Seog Bae (Springer Nature, 2025)
Piezo2, a mechanosensitive ion channel, serves as a crucial mechanotransducer in dental primary afferent (DPA) neurons and is potentially involved in hypersensitivity to mild mechanical irritations observed in dental patients. Given Piezo2's widespread expression across diverse subpopulations of DPA neurons, this study aimed to characterize the mechanosensory properties of Piezo2-expressing DPA neurons with a focus on distinct features of voltage-gated sodium channels (VGSCs) and neuropeptide profiles. Using whole-cell patch-clamp recordings, we observed mechanically activated action potentials (APs) and classified AP waveforms based on the presence or absence of a hump during the repolarization phase. Single-cell reverse transcription polymerase chain reaction combined with patch-clamp recordings revealed specific associations between AP waveforms and molecular properties, including tetrodotoxin-resistant VGSCs (NaV1.8 and NaV1.9) and TRPV1 expression. Reanalysis of the transcriptomic dataset of DPA neurons identified correlations between neuropeptides-including two CGRP isoforms (alpha-CGRP and beta-CGRP), Substance P, and Galanin-and the expression of NaV1.8 and NaV1.9, which were linked to defined AP subtypes. These molecular associations were further validated in Piezo2+ DPA neurons using fluorescence in situ hybridization. Together, these findings highlight the electrophysiological and neurochemical heterogeneity of Piezo2-expressing DPA neurons and their specialized roles in distinct mechanosensory signal transmission.